1995
DOI: 10.1037/0278-6133.14.3.265
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial predictors of AIDS risk behavior and drug use behavior in homeless and drug addicted women of color.

Abstract: The present study examined a causal model consisting of personal and social resources, threat appraisal processes, coping styles, and barriers to risk reduction as predictors of general AIDS risk and specific drug use behaviors among homeless African American (N = 714) and Latina (N = 691) women. The model, which was based on a stress and coping framework, supported many of the hypothesized relationships. Active coping was associated with fewer general AIDS risk behaviors for both groups and less specific drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 42 publications
3
39
0
Order By: Relevance
“…As an example, abused women who subsequently report low self-esteem, may also display less assertiveness with their partners regarding birth control or unwanted sex, or may attempt to increase their self-worth by having multiple sexual partners (Amaro & Raj, 2000;Noell et al, 2001). Nyamathi, Stein, and Brecht (1995) found that lower self-esteem predicted more barriers to condom use in a sample of homeless African-American women. However, greater self-esteem directly predicted active coping styles that in turn were associated with less drug use (Nyamathi et al, 1995).…”
Section: Implications For Interventionmentioning
confidence: 88%
See 1 more Smart Citation
“…As an example, abused women who subsequently report low self-esteem, may also display less assertiveness with their partners regarding birth control or unwanted sex, or may attempt to increase their self-worth by having multiple sexual partners (Amaro & Raj, 2000;Noell et al, 2001). Nyamathi, Stein, and Brecht (1995) found that lower self-esteem predicted more barriers to condom use in a sample of homeless African-American women. However, greater self-esteem directly predicted active coping styles that in turn were associated with less drug use (Nyamathi et al, 1995).…”
Section: Implications For Interventionmentioning
confidence: 88%
“…Nyamathi, Stein, and Brecht (1995) found that lower self-esteem predicted more barriers to condom use in a sample of homeless African-American women. However, greater self-esteem directly predicted active coping styles that in turn were associated with less drug use (Nyamathi et al, 1995).…”
Section: Implications For Interventionmentioning
confidence: 88%
“…32,37,38 Poor coping behaviors such as use of drugs or alcohol are common and are associated with more risky behaviors for HCV infection. [39][40][41] A metaanalysis of interventions to prevent HCV seroconversion among IDUs indicated that multidisciplinary programs may be more beneficial than single intervention programs. 42 For instance, an HCV intervention program for homeless youth, focusing on problem solving skills and strategies to remain HCV uninfected, produced a 29 % greater decline in overall injection risk 6 months post-intervention relative to the control group.…”
Section: Homelessness Intensifies Hcv Risk Behaviorsmentioning
confidence: 99%
“…However, several empirical studies (El-Bassel et al, 1996;Rhoads, 1983) have demonstrated significant findings regarding coping strategies used by either drug abusing or incarcerated women. One relevant study was conducted by Nyamathi, Stein, and Brecht (1995), who found that homeless women tend to utilize avoidant vs. active coping strategies, and that drug use was predicted by avoidant coping strategies.…”
Section: Psychosocial Problems Related To Homelessnessmentioning
confidence: 99%
“…This paraDrug use and homeless women 803 digm has been previously used as a conceptual framework used to investigate social support, coping, and drug abuse among impoverished women (e.g., Nyamathi, Stein, & Brecht, 1995). The social support-stress-coping model implies that addicted women, under great strain, have reason to abuse substances and a greater need for social resources (Tucker, 1982).…”
Section: Theoretical Positionmentioning
confidence: 99%